In vitro Antimicrobial Activity of the Volatile Oil of Nigella Sativa Linn Seeds - Ara, Nazma; Choudhury, SAR; Amin, Ruhul (TAJ: Journal of Teachers Association, 2009)
The in-vitro antimicrobial activity of the Volatile oils of Nigella Sativa Linn Seeds was tested against fifteen pathogenic microbial strains includung three gram-positive, eleven gramnegative and a yeast Candida albicans. The volatile oil showed strong sensitivity to all the organisms. The zone of inhibition was found 13-32mm at a dose of 600μg/disc. Minimum inhibitory concentration (MIC) of the volatile oil was also determined against Staph. Aureus ATCC and E.coli ATCC were found 187μg/ml and 375μg/ml respectively. doi: 10.3329/taj.v18i2.3177 TAJ 2005; 18(2): 109-112